Pemanfaatan Komik Digital sebagai Iklan Layanan Masyarakat Hari Bawa Bekal Nasional di Puskesmas Purwokerto Utara 2 - Prita Suci Nurcandrani; Ade Tuti Turistiati; Antonius Ferdi Widiatmoko (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
Data of the Banyumas District Health Office for 2022 shows that in the 15-24 year age group, 3 to 4 out of 10 teenagers suffered from anemia. The 2013-2018 Riskesdas also noted that 32% of teenagers had anemia. Other findings were obesity, chronic energy deficiency, and eating disorders or unhealthy eating behaviors of teenagers’ lifestyles. Total of 1,150 students classified as teenagers is the responsibility of the Puskesmas Purwokerto Utara 2 to intervene more intensively. As a partner, Puskesmas needs promotional media applied to increase the nutritional status of teenagers. The method used is designing and socializing the use of digital comics. This comic is a form of public service advertisement used as one of the original National Bring Bekal Day social marketing strategies owned by partner. The results of this activity are in accordance with the planned stages by the team and the handover of comics with partner.